Effect of Lactobacilli sources on Escherichia coli and Staphylococcus aureus adherence to uroepithelial cells - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
The inhibitory action of four lactobacilli isolates Lactobacillus bulgaricus, L. acidophilus, L. plantarum and L. fermentum, isolated from four different samples; yoghurt, vinegar, saliva and vagina respectively, on Escherichia coli and Staphylococcus aureus adhesion to uroepithelial cells were investigated. Results showed that all Lactobacillus isolates or their supernatant were able to reduce the number of the uropathogens attached to uroepithelial cells. However, inhibition level of lactobacilli cells was higher than their supernatant. Nevertheless, the human indigenous lactobacilli (L. fermentum and L. plantarum) were more competitive than food lactobacilli (L. acidophilus and L. bulgaricus).